6LoWPAN Routing Issues (International Journal of Engineering and Computer Science, 2014)
6LoWPAN (IPV6 over Wireless Personal Area Network) is a wireless personal area network that contain devices compatible with IEEE 802.15.4. Routing is the major issue in 6LoWPANs as the nodes are characterised by scarce memory, limited power, low battery life, limited resources and less cost. Routing protocols for such networks should be designed such that they make efficient use of available resource and should exhibit high performance. This paper presents a detailed survey of 6LoWPAN routing protocols, their comparison on several metrics such as memory power, power consumption, scalability, routing type, location information and many other factors.